Global actions for the prevention of child abuse - Flecha García, Ramón; Pulido Rodríguez, Cristina (Avances en Supervisión Educativa, 2009)
The prevention of abuse to children on Internet has generated over the last years a global social concern. In the international forums in which the minors themselves have voiced their ideas, claim a needed international coordination from different fields (legal, media, education, government, companies, etc.) to work ensemble for its prevention. This article presents some of the data that describe how the abuse to children has been brought to light in this historical moment as a global social problem to eradicate, and it also presents the global action lines promoted internationally besides offering some examples.